Hypertension and stroke - Kloch-Badełek, Małgorzata; Czarnecka, Danuta; Wiliński, Jerzy (Przewodnik Lekarza/Guide for GPs, 2008)
Hypertension, the most frequent risk factor of stroke, is a factor that can be modified. Data from clinical studies indicate that respective benefits result mostly from the reduction of arterial pressure. According to the guidelines we can use all available hypotensive drugs and their rational combinations to achieve this target. Presently there are no guidelines referring to optimal systolic and diastolic pressure values or reduction of the systolic pressure below 140 mm Hg and the diastolic one below 90 mm Hg. Including hypotensive treatment in the first hours after stroke is still controversial. In spite of the well documented importance of arterial pressure reduction it is difficult to determine the optimal moment when we should begin the lowering of arterial blood pressure after a recent stroke episode and also to select the most suitable hypotensive therapy because there are no studies comparing different hypotensive drugs in the secondary prevention of stroke.